New modes of governance and the Irish case: finding evidence for explanations of social partnership - Adshead, Maura (Economic & Social Studies, 2006)
This paper applies insights from governance and multi-level governance(MLG) studies to the analysis of Social Partnership in order to: (1) outline a methodological approach for the study of Social Partnership over time; and (2) to provide neutral framework for analysis that will facilitate the collection of empirical evidence that may contribute (either positively or negatively) to the theorising of Social Partnership as a new form of governance. The proposed methodology focuses on the extent of policy integration (and/or disaggregation) between policy interests in the Social Partnership model in order to ascertain how inclusive Irish Social Partnership is. This is considered to be important, given the variety of claims made for Social Partnership as an instrument of direct and participatory democracy.
This paper was delivered at a conference ?Social Partnership: A New Kind of Governance?? funded by the Irish Research Council for the Humanities and Social Sciences, National Institute for Regional and Spatial Analysis and the Department of Sociology, NUI Maynooth, 14-15 September 2004.
Keywords: Social partnership; Governance; Ireland